Uji Pemberian Kompos Azolla microphylla Pada Pertumbuhan Bibit Karet (Hevea brasiliensis) Stum Mini - Indriati Meilina Sari; Sampoerno '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aim to determine the effect of compost on the growth of Azolla microphylla PB 260 clone rubber seedlings mini stump. This research has been conducted at Agriculture Faculty, University of Riau starting from April to July 2013. The research was carried out experimentally using completely randomized design non factorial consisting of 4 treat ments and 3 replications, obtained 12 experimental units and each unit consists of 3 seeds so that total earned is 36 rubber seedlings and as sample 2 seedlings per unit experiment. Compost treatment given to the provision of treatment levels; 0, 15, 30 and 45 g/polybag (0, 10, 20 and 30 ton/ha) mixed by weighing soil 3 kg. The data were statistically analyzed using analysis of variance, followed by Duncan's test New Multiple Range Test (DNMRT) at the level of 5%. Parameters observed are lenght of grafting (cm), stem graft girth (cm), number of leaves (sheet), leaf area (cm²) and shoot root ratio (g). Giving Azolla microphylla compost on growing mini stump rubber seedling significantly effect on extending the graft and number of leaves. Meanwhile, for stem graft girth, leaf area and shoot root ratio reveal not significant. Compost dosing 30 g/polybag shows the best results for the growth of rubber seedlings mini stump compared them 0, 15 and 45 g/polybag. Keywords – Rubber seeds mini stump, Azolla microphylla compost, dose